Use of Barbed Sutures for Congenital Diaphragmatic Hernia Repair - Nadine R. Muensterer; Elena Weigl; Anne-Sophie Holler; Christiane Zeller; Beate Häberle; Oliver J. Muensterer (MDPI AG, 2023)
Background: Congenital diaphragmatic hernia (CDH) repair can be challenging, particularly when a larger defect is present. Barbed sutures prevent the suture from slipping back after approximation of the tissues. Although introduced almost 2 decades ago, barbed sutures have not been widely used for CDH repair. We report our initial experience and pitfalls. Methods: All patients presenting with CDH from 2021 onward underwent repair using barbed sutures. Demographics, operative parameters, complications, and outcomes were prospectively recorded. Results: A total of 13 patients underwent CDH repair during the study interval (median age 6 days, range 3 days to 5.75 years). Median operative time was 89 min (range 46 to 288 min). Five thoracoscopic and eight open procedures were performed. Severe pulmonary hypertension and ECMO (extracorporeal membrane oxygenation) were considered contraindications for thoracoscopic repair. The included patients were compared to a historic controlled group performed without barbed sutures. The barbed suture facilitated easy and quick closure of the defects in most cases and obviated the need for knot tying. One patient in the thoracoscopic group had a patch placed due to high tension after the barbed sutures tore the diaphragm. At a median follow-up time of 15 months (range 2 to 34 months), one patient had died, and one patient with complete diaphragmatic agenesis was home-ventilated. There were no recurrences. Median operative time trended lower (89 min) than in the historic control group repaired without barbed sutures (119 min, p < 0.06) after eliminating outliers with large, complex patch repairs. Conclusions: Barbed sutures simplify congenital diaphragmatic hernia repair regardless of whether a minimal-invasive or open approach is performed. Patch repair is not a contraindication for using barbed sutures. The resulting potential time savings make them particularly useful in patients with cardiac or other severe co-morbidities in which shorter operative times are essential. In cases with high tension, though, the barbs may tear through and produce a "saw" effect on the tissue with subsequent damage.